Las estrategias didácticas para el proceso de mediación lectora en Educación Básica Superior y Bachillerato en centros educativos urbano y rural - Rojas Armijos, Fernando Jose (2024)
This research arises from the need to understand the teaching strategies used by Language and Literature teachers during the reading mediation process (pre-reading, reading, and post-reading) in two institutional typologies: urban and rural. The objective of the study was to analyze teaching strategies at the levels of upper basic education and high school levels. The approach of this research is qualitative and field-based; data collection instruments included non-participatory observation and interviews. The results reveal the teaching strategies employed by the teachers. In the pre-reading stage within the rural context, strategies with a playful purpose were predominant, such as riddles, "tingo tango," "my little boat is loaded with," and questions about the title of the reading. In the urban context, teaching strategies focused on activating prior knowledge were used, aimed at contextualizing the reading, its author, and its social and cultural background. During the reading stage, both rural and urban contexts utilized strategies based on different reading modalities, such as independent reading, shared reading, commented reading, and reading in turns. A notable finding in the urban context is the inclusion of individual or home reading. In rural settings, teachers often rely on readings suggested by the Ministry of Education textbooks and short excerpts, unlike the urban context, where complete works from the literary canon are used, with minimal or no reliance on excerpts. In the post-reading stage, rural contexts were characterized by strategies aimed at text construction, such as creating alternative endings, paraphrasing, and organizing forums to enhance reading comprehension. These also encouraged oral participation and creative writing strategies. In the urban context, teaching strategies were aligned with academic writing, including essays, critical commentary, highlighting main and secondary ideas and thesis statement, and preparing presentations.